The future of extension: A network emergence perspective from the case of the Global Forum for Rural Advisory Services - Davis, Kristin E.; Dolly, David; Lamm, Alexa J.; Lamm, Kevan W. (Association for International Agricultural and Extension Education, 2019)
Extension, as a socially-based institution, must constantly evolve with society. This case study on the Global Forum for Rural Advisory Services uses social network theory to add to the literature on network emergence in the context of extension. The researchers explored how an extension network evolved in response to global agricultural issues. The use of a qualitative content analysis of the eight themes of the annual meeting of the network showed how the Forum changed in response to current events and regional needs. The Forum first built and consolidated a network of global extension members and then moved to an outward focus in terms of relations within and outside of extension. Analysis revealed the network first focused on simple, basic themes of interest to the knowledge network, and slowly expanded to wider and more complex topics that involved a richer network of actors. This case implies that extension institutions, which are on the front line of trends stemming from societal shifts, are thus positioned to play a crucial role in technology transfer and sensitization of global agricultural issues.